2019
DOI: 10.1016/j.cub.2019.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Rat Orbitofrontal Ensemble Activity Contains Multiplexed but Dissociable Representations of Value and Task Structure in an Odor Sequence Task

Abstract: Highlights d OFC ensembles multiplex information about task structure and value d Information about task structure is dissociable and constrained by task relevance d OFC uses a persistent code to represent this task-relevant structural information d The structural representation in OFC predicts behavior, even on ''incorrect'' trials

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 44 publications
10
68
0
Order By: Relevance
“…Our result matches a large body of work in human and non-human primates. It also confirms and extends previous observations in rodents (Gremel and Costa, 2013;Hirokawa et al, 2017;Roitman and Roitman, 2010;Sul et al, 2010;van Duuren et al, 2009;Zhou et al, 2019). Interestingly, one earlier study in rats failed to find any systematic relation between the effects induced by changes in reward quantity and those induced by changes in delay (Roesch et al, 2006).…”
Section: Representation Of Subjective Values In Losupporting
confidence: 91%
See 1 more Smart Citation
“…Our result matches a large body of work in human and non-human primates. It also confirms and extends previous observations in rodents (Gremel and Costa, 2013;Hirokawa et al, 2017;Roitman and Roitman, 2010;Sul et al, 2010;van Duuren et al, 2009;Zhou et al, 2019). Interestingly, one earlier study in rats failed to find any systematic relation between the effects induced by changes in reward quantity and those induced by changes in delay (Roesch et al, 2006).…”
Section: Representation Of Subjective Values In Losupporting
confidence: 91%
“…Consistent with this understanding, LO lesions in rodents (Gallagher et al, 1999;Gremel and Costa, 2013) and OFC lesions in primates (Izquierdo et al, 2004;Reber et al, 2017;Rudebeck and Murray, 2011;West et al, 2011) induce similar effects on goal-directed behavior under reinforcer devaluation. A series of studies found evidence consistent with a neuronal representation of value and other decision variables in LO (Feierstein et al, 2006;Hirokawa et al, 2017;Roitman and Roitman, 2010;Sul et al, 2010;van Duuren et al, 2008;van Duuren et al, 2009;Zhou et al, 2019). For example, van Duuren and colleagues showed that neurons in LO reflects both the magnitude and the probability of upcoming rewards.…”
Section: Introductionmentioning
confidence: 94%
“…Recent rodent and human work support this proposal with findings that vmPFC representations are goal-specific in nature, at least at the end of learning. Specifically, neural ensembles in the rodent homolog of vmPFC have been demonstrated to represent higher order goal states that relate stimuli to behaviorally relevant value 10,11,25 . Similarly, one human neuroimaging study recently localized representations of a complex task space relating 16 different task states to vmPFC activation patterns 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This compression process is goal-directed and akin to how attention in category learning models dynamically selects features that have proven predictive across recent learning trials 8,9 . Although emerging evidence suggests structured representations occur in the rodent homolog of vmPFC 10,11 , such coding in human vmPFC remains poorly understood. Here, we directly assess the data reduction hypothesis by leveraging an information-theoretic approach in human neuroimaging to measure how goal-driven learning is supported by attention updating processes in vmPFC.…”
mentioning
confidence: 99%
“…This proposal was initially inspired by the discovery of place cells [15,16] but was later extended to nonspatial information about objects [17], time [18], and relational knowledge [19]. More recently, rodent and human studies on decision-making have proposed that the orbitofrontal cortex (OFC) also plays a key role in representing and utilizing cognitive maps for organizing behavior directed at obtaining rewards [9,[20][21][22][23][24]. The suggestion that both HPC and OFC encode task-relevant information raises questions about how representations in these two areas are related and how OFC and HPC interact to support model-based behavior.…”
Section: Introductionmentioning
confidence: 99%